Day 1 Tue, September 30, 2014 2014
DOI: 10.2118/171651-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microbes in Hydraulic Fracturing of Montney Tight Gas Formations in Western Canada

Abstract: Microbes in unconventional gas operations can conceivably contribute to (i) degradation of polymers in hydraulic fracturing fluid, (ii) well plugging, limiting gas flow and (iii) souring and corrosion due to activity of sulfate reducing bacteria (SRB). Flowback waters from a tight gas field in Northern British Columbia were distinct from the fresh water, used for making hydraulic fracturing fluid, by their high salinity, low pH and high ammonium concentrations. Microbial counts of SRB and of acid-producing bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…There is no evidence of this in this study as indicated also elsewhere (Elliott et al, 2014). The high temperatures of Montney shale gas fields (70-100°C), caused by their location at depths of 2500 mbs or more, combined with the high salinity (Ͼ2 Meq of NaCl) and a low pH of this environment prevents microbial growth.…”
Section: Taxon (Class; Order; Family; Genus) B_sw B_pwscontrasting
confidence: 44%
See 2 more Smart Citations
“…There is no evidence of this in this study as indicated also elsewhere (Elliott et al, 2014). The high temperatures of Montney shale gas fields (70-100°C), caused by their location at depths of 2500 mbs or more, combined with the high salinity (Ͼ2 Meq of NaCl) and a low pH of this environment prevents microbial growth.…”
Section: Taxon (Class; Order; Family; Genus) B_sw B_pwscontrasting
confidence: 44%
“…Samples were obtained from a shale gas field in the Montney formation in NE BC, located at 2500 m below the surface (mbs), where the resident temperature is 75-100°C (Elliott et al, 2014). Samples were also obtained from a shale oil field in the Bakken formation, located at 1000 mbs with a resident temperature of 30-35°C.…”
Section: Collection Of Samples and Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrocarbon resources represent an important global energy source, currently providing over 75% of primary energy in the United States (U.S. Department of Energy et al, 2020b), and also play an essential role in other countries including Canada and the United Kingdom (Stevens, 2013;Elliott et al, 2014;Rivard et al, 2014). The majority of fossil fuels are currently extracted from unconventional wells using advanced technologies, including horizontal drilling and hydraulic fracturing (U.S. Department of Energy et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies report the presence of bacteria in produced water, 2−4,9,12−15 although a number of studies have found few to no bacteria present. 6,8 Of those studies in which bacteria were found, the Marcellus shale formation shows an eventual dominance by halotolerant sulfidogenic organisms, 2,3 while other shale plays seem to exhibit highly diverse microbial consortia. 4,9,12,13,15 H 2 S gas may also arise from geochemical sources 18 and has been shown to originate from the interaction of hydrocarbons with sulfur-bearing minerals such as anhydrite (CaSO 4 ), at 284 °F, 19 via the following reaction:…”
Section: ■ Introductionmentioning
confidence: 99%